Physical, chemical and sensory changes of refrigerated yellow pitahaya treated preharvest with 1-mcp (2013)
The effect of application of 0, 200 and 400 mg L-1 aqueous solution of 1-methylcyclopropene (1-MCP) on preharvest yellow pitahaya (Selenicereus megalanthus Haw) was assessed. Changes in weight loss, total change of color, total sugars, titratable acidity, ascorbic acid and sensory analysis were measured. The pitahaya was stored under refrigeration (10 °C and 85% relative humidity for 29 days). Two types of packaging were used (export cartons and perforated plastic crates, used in the domestic market). Results showed that during storage, the chilled yellow pitahaya presented significant variations in all response variables. However, the application of aqueous solutions of 1-MCP before harvesting, produces significant beneficial effects on the chemical, physical and sensory properties of yellow pitahaya and extends their shelf life by 5 days.